Genetic portrait of Jewish populations based on three sets of X-chromosome markers: Indels, Alu insertions and STRs. (November 2017) - Ferragut, J.F.; Bentayebi, K.; Pereira, R.; Castro, J.A.; Amorim, A.; Ramon, C.; Picornell, A.
Highlights: A database of 53 X-chromosome loci for populations with Jewish ancestry is provided. One Sephardic isolate (Chuetas) and their host population were also studied. The results obtained demonstrated their usefulness for general forensic purposes. Specific databases for differentiated Jewish populations should be used. Results suggest a generally sex-biased demographic history in Jewish populations. Abstract: Population genetic data for 53 X-chromosome markers (32 X-indels, 9 X-Alu insertions and 12 X-STRs) are reported for five populations with Jewish ancestry (Sephardim, North African Jews, Middle Eastern Jews, Ashkenazim, and Chuetas) and Majorca, as the host population of Chuetas. Genetic distances between these populations demonstrated significant differences, except between Sephardic and North African Jews, with the Chuetas as the most differentiated group, in accordance with the particular demographic history of this population. X-chromosome analysis and a comparison with autosomal data suggest a generally sex-biased demographic history in Jewish populations. Asymmetry was found between female and male effective population sizes both in the admixture processes between Jewish communities, and between them and their respective non-Jewish host populations. Results further show that these X-linked markers are highly informative for forensic purposes, and highlight the need for specific databases for differentiated Jewish populations.